Association between Teachers’ Selflessness and School Organizational Commitment - Jimenez, Edward, C; Jimenez, Roda, S (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2022)
This study aimed to determine the relationship between teachers' selflessness on their school organizational commitment. The study employed a descriptive-correlation research design with the online survey as the primary data collection tool. The respondents came from the 30 elementary and secondary schools in the Schools Division Office, Central Luzon. One hundred fifty-one public school teachers participated in the online survey using a stratified sampling technique. Adapted questionnaires were used to gather data. For the statistical treatment of the study, the mean was used for the teachers' responses. In contrast, for the relationship, the study used Pearson r-correlation. The study found that teachers' selflessness described their philosophies as "agree." As for the teachers' organizational commitment, it generated moderate to high responses. There is a significant difference in teachers' selflessness regarding sex and position. Also, the study found a relationship between teachers' selflessness, and affective and continuance commitment aspects of teachers' organizational commitment. Based on the results mentioned above, the researcher provided some crucial recommendations for the study.